Governmental Efforts on Homeland Security and Crime: Public Views and Opinions - Penn, Everette B. (American journal of criminal justice, 2009)
This paper examines views of the respondents regarding homeland security and traditional crime in the United States. Using questions from the 2007 Penn State Poll, a sample of 862 Pennsylvanians participated through a telephone interview. Participants were questioned about their concerns regarding the effectiveness of homeland security, their fear of crime (white-collar, property, violent and terrorist attacks). The results revealed that citizens were satisfied with the effectiveness of homeland security since the September 11, 2001, attacks. The results indicate that fear of crime is different for demographics, and we were able to show that those that thought homeland security had been effective increased the likelihood of fear of white-collar crime. We were also able to show demographic differences for national spending on crime. In addition, we were able to show that those who believed that homeland security was effective did not believe that national spending was at the proper level for property, violent, or white-collar crime. The implications of these results are discussed.